Cardiovascular disease risk factors and outcomes of acute myocardial infarction in young adults in two nationwide cohorts in the united states. (11th May 2022) - Mishra, V; Desai, R; Chhina, AK; Raina, J; Itare, V; Patel, M; Doshi, R; Gangani, K; Sachdeva, R; Kumar, G
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Acute myocardial infarction (AMI) can have considerable morbidity and devastating socioeconomic and psychological consequences in young adults. Previous studies reveal that the decline in mortality in AMI has mainly been in the older population while being comparatively less significant in younger patients. This study compares young adults (18 to 44 years) hospitalized with AMI across two nationwide cohorts, 2007 and 2017, in the United States (US). It examines the burden of AMI hospitalizations, the prevalence of comorbidities, and in-hospital outcomes in young adults a decade apart. It highlights the rise in AMI hospitalizations, lack of decrease in mortality, sex-based and racial disparities, the surge in post-MI complications, and the decline in reperfusion interventions in young AMI patients over a decade. Purpose: Coronary heart disease prevalence is challenging to ascertain in younger adults because of limited data and frequent silent clinical presentations. AMI and its complications can cause considerable morbidity, psychological trauma, and socioeconomic burden in the young. Methods: We identified hospitalizations for AMI in young adults in 2007 and 2017 using the weighted data from the National Inpatient Sample (NIS), which covers 20% of stratified data of all non-federal community hospitals in the US. We compared the following data between the two cohorts: admission rates, sociodemographic features, in-hospital morbidity, complications, mortality, rate of coronary interventions, and healthcare utilization between the two cohorts. We used Pearson's Chi-square test and Mann-Whitney U test to compare categorical and continuous variables, respectively. We also applied multivariable regression analyses to assess and compare the risk of cardiovascular complications and in-hospital mortality while controlling for confounders, including age, sex, race, median household income quartile, primary insurance enrolment, and pre-existing comorbidities. Results: AMI's incidence was higher in males in both the cohorts, although with a decline (71.1% vs 66.1%), whereas it rose from 28.9% to 33.9% in females. Hypertension (47.8% vs 60.7%), smoking (49.7% vs 55.8%), obesity (14.8% vs 26.8%), and diabetes mellitus (22.0% vs 25.6%) increased in the 2017 cohort (Table 1). We found no significant difference in all-cause mortality (aOR = 1.01 (0.93-1.10), p=0.749). Post-AMI complications, cardiogenic shock (aOR = 1.16 (1.06-1.27), p=0.001), and fatal arrhythmias increased. Reperfusion interventions decreased in the 2017 cohort (PCI; aOR=0.95 (0.91-0.98), p<0.001; CABG; aOR=0.66 (0.61-0.71), p<0.001) (Table 2). Conclusion: Our study highlights the rise in AMI hospitalizations, plateauing of mortality, gender disparity, the surge in post-MI complications, and a reassuring decline in the requirement of reperfusion interventions in young AMI patients over a decade.